Al3Ti Formation By Diffusion Of Aluminum Through Titanium (Latakia University Journal -Basic Sciences Series, 2022)
In this research, some new aspects of  thermal interactions in Al/Ti bilayers contaminated with oxygen of interface have been studied.After annealing process at 460 ⁰C the Al3 Ti phase has been formed at interface where some Al atoms diffused through Ti layer in order to build phase on free surface.During this process the Al quantities on free surface are comparable with the same quantities at the interface but  the center profile nucleation of Al/Ti at interface are inappropriate. Therefore ,the competition between both growths profile and diffusion of Al to free surface.When the completely cover reaches at interface with Al/Ti, then the Al diffusion towards free surface become little.